Implementation and Analysis of Time-Driven Activity-Based Costing (TDABC) - Jalilzada, Jalil; Guliyev, Tural (My University, 2026)
This study investigates the implementation and analysis of a new costing method called Time-Driven Activity-Based Costing (TDABC) system in one of Azerbaijan's prominent beverage producers, known as AZGRANATA, specializing in the production of both alcoholic and non-alcoholic beverages. Since the current traditional costing system implemented by the company, it identifies the significance of a new costing method that is called TDABC due to the possibility of inefficiencies occurring. The new costing method is suggested to address miscalculations and cost distortion issues that may arise within the company, especially from the perspective of juice production. The main purpose of this study is to examine the integration of the TDABC model that effectively responds to the drawbacks of the traditional costing system mechanism, and it is supported by identifying two main factors, including the unit cost of supplying capacity and the time required to complete each activity. Both qualitative and quantitative data were used in this study to measure and compare production costs of the five different juice products, such as Pomegranaze, Nature Best, Poju, Red Crown, and Tetra Park, produced by the company. The main results indicated that the traditional costing method revealed inefficient allocation of indirect costs; however, the application of TDABC provided accurate cost information towards the actual utilization of resources and activities involved in roduction. The study concludes that the application of TDABC supports achieving the successful clarification of cost inaccuracies and contributes to improving the efficiency of resource utilization in juice production. Therefore, the examination of TDABC with real practices involved in the company will help to understand cost behavior systematically and make sustainable decisions about resource allocation, production, and pricing in order to achieve higher profitability and improve operational performance.
Keywords: Time-Driven Activity-Based Costing (TDABC); AZGRANATA; Cost Accuracy; Juice Production; Resource Allocation; Cost Efficiency